Prehabilitation during a pandemic: preoperative exercise to improve fitness in patients undergoing complex surgery for cancer of the lung or oesophagus, the PRE-HIIT trial: an updated study protocol - Normand, Charles; O'Neill, Linda (My University, 2021)
Background: Pre-operative fitness is an established predictor of postoperative outcome; accordingly, targeting pre-operative fitness through exercise prehabilitation has logical appeal. Exercise prehabilitation for patients with cancer of the lung or oesophagus is challenging to implement due to the short opportunity for intervention between diagnosis and surgery. In addition, there are now additional challenges to providing prehabilitation during the coronavirus disease 2019 (COVID-19) pandemic due to concerns about social distancing and minimising patient contact. The PRE-HIIT project will examine the influence of virtually delivered exercise prehabilitation on physiological outcomes and postoperative recovery. Methods: The PRE-HIIT randomised controlled trial (RCT) will compare a 2-week high intensity interval training programme to standard preoperative care in a cohort of patients with thoracic and oesophageal cancers. A protocol for this study has been published previously. As a result of the COVID-19 pandemic, changes to the study assessment battery and the mode of intervention delivery have been made. The PRE-HIIT programme will now be a home-based intervention. Both the exercise intervention and standard care will be delivered via telehealth. The recruitment target for the study remains 78 participants. There is no change to the primary outcome of the study; cardiorespiratory fitness. Secondary outcomes include measures of pulmonary and physical function, quality of life and post-operative morbidity. Outcomes will be measured at baseline and post-intervention. The impact of PRE-HIIT on well-being will be examined qualitatively with interviews post-intervention (T1). This revised protocol will also explore participant’s satisfaction with delivery of prehabilitation via telehealth. The healthcare costs associated with the PRE-HITT programme will also be examined. Discussion: The overall aim of this RCT is to examine the effect of tailored, individually prescribed high intensity interval training on pre-operative fitness and postoperative recovery for patients undergoing complex surgical resections. Trial registration: ClinicalTrials.Gov NCT03978325 07/06/2019
PUBLISHED
Keywords: Telehealth; Multidisciplinary rehabilitation; Exercise; Diet; Education; Cancer